Online versus online plus face-to-face class: The case of International Economics and International Finance - Kurihara, Yutaka (Archives of Business Research, 2022)
COVID-19 has not ended yet and most colleges and universities all over the world could not yet resume face-to-face classes, instead having had to conducted online classes. This situation was common in 2020, however, the situation has gradually changed since 2021. From the changing of delta strains to omicron strains of COVID-19, there were some periods that the number of critically ill patients had decreased rapidly. Most colleges and universities in Japan have transitioned back to face-to-face classes during the semester from online classes. This study examines how the outcome of online class versus online plus face-to-face class changed empirically. The empirical results using difference-in-difference show that introducing face-to-face classes increased the outcome of learners’ performances. While online classes do have some merits, reintroducing face-to-face classes increases learner outcome to a greater extent. Flipped classrooms could give us some good roads to promote the class outcomes.